Editor's Choice – Nationwide Analysis of Patients Undergoing Iliac Artery Aneurysm Repair in the Netherlands. (July 2020) - Jalalzadeh, Hamid; Indrakusuma, Reza; Koelemay, Mark J.W.; Balm, Ron; Van den Akker, L.H.; Van den Akker, P.J.; Akkersdijk, G.J.; Akkersdijk, G.P.; Akkersdijk, W.L.; van Andringa de Kempenaer, M.G.; Arts, C.H.; Avontuur, J.A.; et al.
Abstract : Objective: The new 2019 guideline of the European Society for Vascular Surgery (ESVS) recommends consideration for elective iliac artery aneurysm (eIAA) repair when the iliac diameter exceeds 3.5 cm, as opposed to 3.0 cm previously. The current study assessed diameters at time of eIAA repair and ruptured IAA (rIAA) repair and compared clinical outcomes after open surgical repair (OSR) and endovascular aneurysm repair (EVAR). Methods: This retrospective observational study used the nationwide Dutch Surgical Aneurysm Audit (DSAA) registry that includes all patients who undergo aorto-iliac aneurysm repair in the Netherlands. All patients who underwent primary IAA repair between 1 January 2014 and 1 January 2018 were included. Diameters at time of eIAA and rIAA repair were compared in a descriptive fashion. The anatomical location of the IAA was not registered in the registry. Patient characteristics and outcomes of OSR and EVAR were compared with appropriate statistical tests. Results: The DSAA registry comprised 974 patients who underwent IAA repair. A total of 851 patients were included after exclusion of patients undergoing revision surgery and patients with missing essential variables. eIAA repair was carried out in 713 patients, rIAA repair in 102, and symptomatic IAA repair in 36. OSR was performed in 205, EVAR in 618, and hybrid repairs and conversions in 28. The median maximum IAA diameter at the time of eIAA and rIAA repair was 43 (IQR 38–50) mm and 68 (IQR 58–85) mm, respectively. Mortality was 1.3% (95% CI 0.7–2.4) after eIAA repair and 25.5% (95% CI 18.0–34.7) after rIAA repair. Mortality was not significantly different between the OSR and EVAR subgroups. Elective OSR was associated with significantly more complications than EVAR (intra-operative: 9.8% vs. 3.6%, post-operative: 34.0% vs. 13.8%, respectively). Conclusion: In the Netherlands, most eIAA repairs are performed at diameters larger than recommended by the ESVS guideline. These findings appear to support the recent increase in the threshold diameter for eIAA repair.